3D-QSAR study of microsomal prostaglandin E-2 synthase (mPGES-1) inhibitors - San Juan, Amor A.; Cho, Seung Joo (SPRINGER, 2007)
Microsomal prostaglandin E-2 synthase (mPGES-1) has been identified recently as a novel target for treating pain and inflammation. The aim of this study is to understand the binding affinities of reported inhibitors for mPGES-1 and further to design potential new mPGES-1 inhibitors. 3D-QSAR-CoMFA (comparative molecular field analysis) and CoMSIA (comparative molecular similarity indices analysis) - techniques were employed on a series of indole derivatives that act as selective mPGES-1 inhibitors. The lowest energy conformer of the most active compound obtained from systematic conformational search was used as a template for the alignment of 32 compounds. The models obtained were used to predict the activities of the test set of eight compounds, and the predicted values were in good agreement with the experimental results. The 3D-QSAR models derived from the training set of 24 compounds were all statistically significant (CoMFA; q(2) = 0.89, r(2) = 0.95, r(bs)(2) = 0.98, r(pred)(2) = 0.83 and CoMSIA; q(2) = 0.84, r(2) = 0.93, r(bs)(2) = 0.93, r(pred)(2) = 0.94). Contour plots generated for the CoMFA and CoMSIA models reveal useful clues for improving the activity of mPGES-1 inhibitors. In particular, substitutions of an electronegative fluorine atom or a bulky hydrophilic phenoxy group at the meta or para positions of the biphenyl rings might improve inhibitory activity. A plausible binding mode between the ligands and mPGES-1 is also proposed.
Keywords: PARTIAL LEAST-SQUARES; COMFA; VALIDATION; PROTEINS; PATHWAY; CELLS; FIELD